What is the best internal fixation in pelvic fracture models with open-book injury and anterior sacroiliac joint disruption? (Faculty of Medicine Universitas Indonesia, 2015)
Background: The best operative management for open-book pelvic injury with anterior sacroiliac disruption (OTA/AO B1.1 classification) is still debated. This biomechanical study aimed to find the best internal fixation technique for such injury. Methods: Open-book injury with anterior sacroiliac joint disruption was simulated on 25 artificial pelvic bones. Twenty five artificial pelvic bones were divided into 5 groups (n=5 /group) and fixated with five different fixation techniques: 1). 1SP+1IS; 2). 2SP; 3). 2SP+2SIP; 4). 1SP+2IS S1, and 5). 1SP+1IS S1+S2. Biomechanical properties of each fixation technique were assessed using Tensilon® RTF-1310 to measure the resistance to translation and load to failure. Data were statistically analyzed using one-way ANOVA followed by post-hoc Bonferroni test. Results: The highest mean load to failure of axial forces (1490.36 N) was achieved by the fixation technique using one symphyseal plate and two iliosacral screws located at S1 dan S2. The addition of one iliosacral screw significantly increased the mean load to failure for axial compression (p<0.05). Conclusion: The addition of sacroiliac joint posterior fixation, either with plate or screw, will increase the fixation biomechanical strength. Single symphyseal plate and two iliosacral screws on S1 and S2 provided the best mechanical resistance to axial loading. Thus, it can be concluded that such fixation technique is best for open-book pelvic injury with anterior sacroiliac disruption.